Trade Creation and Trade Diversion in Deep Agreements - Mattoo, Aaditya; Mulabdic, Alen; Ruta, Michele (World Bank, Washington, DC, 2017)
Preferential trade agreements have boomed in recent years and extended their reach well beyond tariff reduction, to cover policy areas such as investment, competition, and intellectual property rights. This paper uses new information on the content of preferential trade agreements to examine the trade effects of deep agreements and revisit the classic Vinerian question of trade creation and trade diversion. The results indicate that deep agreements lead to more trade creation and less trade diversion than shallow agreements. Furthermore, some provisions of deep agreements have a public good aspect and increase trade also with non-members.